THE EFFECT OF SELLING PRICE SETTING ON VEGETABLE SALES - Roki, Muhammad; Nurmalia, Ana; Yumiati, Yossie; Afriani, Ririn (University of Prof. Dr. Hazairin, SH, 2024)
The importance of nutrients in vegetables for the human body to meet the needs of minerals and vitamins. Indonesians can meet their vegetable needs with various choices at varying prices. This study aims to determine the method of determining the selling price of vegetables and the effect of price determination on the number of sales of vegetable retailers at the Pulau Baai Market in Bengkulu City. The research methods used is qualitative and quantitative. The selection of respondents used the census method totaling 28 people. The analysis used in this study is descriptive analysis and simple linear regression. The results of the study showed that vegetable retailers at the Pulau Baai Market in Bengkulu City used the (mark pricing) method in determining prices, where the average markup value for cabbage was IDR 3,096 /kg, tomatoes IDR 2,378 /kg, carrots IDR 3,453 /kg, Chinese cabbage IDR 2,685 /kg, spinach IDR 721 /kg, and kale IDR 255 /kg and vegetables whose pricing affects the number of sales are Chinese cabbage and kale. Meanwhile, the determination of selling prices that do not affect the amount of sales are cabbage, tomatoes, carrots, and spinach.